The Curriculum and Learning System at Daarul Ilmi Integrated Islamic Boarding School, West Bandung - Arif Rahman Hakim; Olivia Ridheta Citrawijaya; Zulaekah Zulaekah; Nurwadjah Ahmad; Andewi Suhartini (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study examines the curriculum and learning system at Curriculum and Learning System at Daarul Ilmi Integrated Islamic Boarding School West Bandung within the framework of integrated Islamic education. Situated in the field of Islamic Education and Curriculum Studies, this research aims to analyze the structure of the Kulliyatul Mu’allimin Al-Islamiyah (KMI) curriculum, its instructional methods, and their implications for the development of students’ academic, linguistic, and character competencies. The KMI model was initially developed by Pondok Modern Darussalam Gontor as a modern Islamic education system that integrates religious and general sciences. This topic is crucial as modern pesantren face challenges in harmonizing religious education, the national curriculum, and mastery of international languages. Therefore, a systematic study is needed to evaluate its effectiveness. Employing a descriptive qualitative approach, data were collected through observation, interviews, and curriculum document analysis. The findings reveal that the KMI curriculum is holistically integrated with the national education system, combining formal, non-formal, and informal learning, with Arabic and English used as primary instructional languages. Such integration simultaneously fosters academic excellence, spiritual growth, and character formation. The contribution of this study lies in presenting an adaptive and relevant model of integrated Islamic education that can serve as a reference for curriculum development in modern Indonesian pesantren